Unlocking Apoptotic Pathways: Overcoming Tumor Resistance in CAR‐T‐Cell Therapy - Zhanna Zhang; Manqi Su; Panruo Jiang; Xiaoxia Wang; Xiangmin Tong; Gongqiang Wu (Cancer Medicine)
ABSTRACT Background Chimeric antigen receptor (CAR)‐T‐cell therapy has transformed cancer treatment, leading to remarkable clinical outcomes. However, resistance continues to be a major obstacle, significantly limiting its efficacy in numerous patients. Objectives This review critically examines the challenges associated with CAR‐T‐cell therapy, with a particular focus on the role of apoptotic pathways in overcoming resistance. Methods We explore various strategies to sensitize tumor cells to CAR‐T‐cell‐mediated apoptosis, including the use of combination therapies with BH3 mimetics, Mcl‐1 inhibitors, IAP inhibitors, and HDAC inhibitors. These agents inhibit anti‐apoptotic proteins and activate intrinsic mitochondrial pathways, enhancing the susceptibility of tumor cells to apoptosis. Moreover, targeting the extrinsic pathway can increase the expression of death receptors on tumor cells, further promoting their apoptosis. The review also discusses the development of novel CAR constructs that enhance anti‐apoptotic protein expression, such as Bcl‐2, which may counteract CAR‐T cell exhaustion and improve antitumor efficacy. We assess the impact of the tumor microenvironment (TME) on CAR‐T cell function and propose dual‐targeting CAR‐T cells to simultaneously address both myeloid‐derived suppressor cells (MDSCs) and tumor cells. Furthermore, we explore the potential of combining agents like PPAR inhibitors to activate the cGAS‐STING pathway, thereby improving CAR‐T cell infiltration into the tumor. Conclusions This review highlights that enhancing tumor cell sensitivity to apoptosis and increasing CAR‐T cell cytotoxicity through apoptotic pathways could significantly improve therapeutic outcomes. Targeting apoptotic proteins, particularly those involved in the intrinsic mitochondrial pathway, constitutes a novel approach to overcoming resistance. The insights presented herein lay a robust foundation for future research and clinical applications aimed at optimizing CAR‐T cell therapies.